تنوع سياسات التشغيل و انعكاساتها على سوق العمل في الجزائر دراسة احصائية خلال الفترة 1970-2018 (El-Wahat Journal for Research and Studies, 2025)
Employment Policies Are An Integral Part Of Economic Development Policy Because Of Their Dimensions And Objectives. For This Reason They Are Of Interest To Most Societies And Countries. Through This Study, We Tried To Address The Most Important Employment Policies Adopted By The Algerian Government As An Attempt To Rebalance The Labor Market. It Has Been Shown By Tracking The Process Of Variables Variables That The Measures And Negative Policies Of Employment Are Revived By The High Frequency Of Investments, Which In Turn Rise With The Rise In Oil Prices In Global Markets. Keywords- Employment Policies, Labor Market, Unemployment, Job Demand And Supply.